Implementation of RFID for security system (i-RSS) in UiTM chancellery office / Nor Azizah Hamzah - Hamzah, Nor Azizah (2015)
I-RSS is a project that focuses on the scope that concentrates on the registration system of UiTM chancellery office. UiTM chancellery office is the hub of the university’s administration. More than 200 visitors visit every month. In terms of functionality, this office provides administrative services to the Vice-Chancellor in carrying out their daily tasks. This project aim is to make registration process for UiTM Chancellery Office visitor runs smoothly by using RFID technology implemented with i-RSS. Currently, a very low technology has been used in order to take registration information. The main objective of this project is to develop system for registration of chancellery’s visitors for security purpose using RFID technology. There used five phase methodology activities in this project which are planning, design system, development system, testing and documentation. Each phases has it owns deliverables that becomes this project findings in order to achieve the objectives of this project. Form the analysis of user that participated in UAT, the result shows that the percentage of admin is 58% and visitor is 42% familiar with that system.